Evaluasi Program Sekolah Unggul Berbasis Soft Skills (Studi Kasus di SMA Negeri 1 Sidoarjo) - Warsiman Warsiman; Karyanto Karyanto; Endang Sulistiyorini (Kelola: Jurnal Manajemen Pendidikan, 2022)
The purpose of this study was to determine the evaluation of the soft skills-based superior school program at SMAN 1 Sidoarjo. This study used the descriptive qualitative method. The subjects of this study were principals, teachers, education staff, students, and all those involved in the soft skills-based superior school program at SMAN 1 Sidoarjo. The instruments of this research are interviews, observations, and documentation. The data findings were analyzed and presented in a qualitative descriptive manner. The results showed that the evaluation of the soft skills-based superior school program at SMAN 1 Sidoarjo was carried out by the internal school itself, and external parties, namely the education office, school supervisors, school committees, and parents/guardians. The results of the study explain that the evaluation is carried out through the following stages: (1) preparation of evaluation instruments; (2) evaluation by internal parties; (3) evaluation by external parties; (4) evaluation results; and (5) follow-up in the form of an improvement plan.